1991
DOI: 10.1046/j.1468-2982.1991.1102069.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of The Brain in Patients With Migraine

Abstract: Magnetic resonance imaging (MRI) was studied in 91 patients with migraine and in 98 controls. Risk factors known to cause MRI lesions were carefully examined. In 36 patients with migraine (39.6%), small foci of high intensity on T2-weighted and proton-density-weighted images were seen in the white matter. Of patients with migraine who were less than 40 years old and without any risk factor, 29.4% showed lesions on MRI; this was significantly higher than the 11.2% for the group of age-matched controls (n = 98).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 19 publications
2
60
1
5
Order By: Relevance
“…2,8,[15][16][17][18][19][20][21][22][23] The populations in these studies were reasonably similar. Results from these studies were combined in a meta-analysis to yield a summary prevalence of 0.0018 (approximately 0.2%), with an upper 95% confidence limit of 0.0059 (approximately 0.6%).…”
Section: Nonacute Headache and Normal Neurological Examinationmentioning
confidence: 99%
“…2,8,[15][16][17][18][19][20][21][22][23] The populations in these studies were reasonably similar. Results from these studies were combined in a meta-analysis to yield a summary prevalence of 0.0018 (approximately 0.2%), with an upper 95% confidence limit of 0.0059 (approximately 0.6%).…”
Section: Nonacute Headache and Normal Neurological Examinationmentioning
confidence: 99%
“…MRA normalse ve hala şüphemiz varsa konvansiyonel anjiografi yapılmalıdır. Karotis doppler incelemesi, akut baş ağ-rısı ile beraber Horner sendromu bulunan olgularda karotis diseksiyonunu dışlamada yardımcıdır [19,20,[24][25][26][27].…”
Section: Discussionunclassified
“…The migraine may be associated with early pathologic changes in the brain. MRI studies in patients with migraine showed focal areas of high intensity on both T2-weighted and proton density-weighted MR images distributed bilaterally in the white matter of the brain [5].…”
Section: Migrainementioning
confidence: 96%
“…In another study, by Igarashi et al [5], the authors assumed that repetition of migraine, with repeated episodes of cerebral hypoperfusion responsible for aura, could cause permanent ischaemic changes in the brain. The characteristics of MRI lesions in migraine were well defined small foci on T2-weighted and proton densityweighted images in the white matter.…”
Section: Migrainementioning
confidence: 99%
See 1 more Smart Citation